Using buffered playtime for QoE‐oriented resource management of YouTube video streaming. Issue 3 (23rd April 2013) - Wamser, F.; Hock, D.; Seufert, M.; Staehle, B.; Pries, R.; Tran‐Gia, P.; Fiedler, Markus; Jiang, Yuming; Zheng, Kan; Chatzimisios, Periklis; Xiang, Wei
ABSTRACT YouTube is the most important online platform for streaming video clips. The popularity and the continuously increasing number of users pose new challenges for Internet service providers. In particular, in access networks where the transmission resources are limited and the providers are interested in reducing their operational expenditure, it is worth to efficiently optimise the network for popular services such as YouTube. In this paper, we propose different resource management mechanisms to improve the quality of experience (QoE) of YouTube users. In particular, we investigate the benefit of cross‐layer resource management actions at the client and in the access network for YouTube video streaming. The proposed algorithms are evaluated in a wireless mesh testbed. The results show how to improve the YouTube QoE for the users with the help of client‐based or network‐based control actions. Copyright © 2013 John Wiley & Sons, Ltd.